2015
DOI: 10.3109/09638288.2015.1024342
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation, reliability and validity of the Turkish version of the Lower Limb Functional Index

Abstract: Turkish version of LLFI was found to be valid and reliable for the measurement of lower limb function in a Turkish population. Implications for Rehabilitation Lower extremity musculoskeletal disorders are common and greatly impact activities among the affected individuals pertaining to daily living, work, leisure and quality of life. Patient-reported outcome (PRO) measures have advantages as they are practical, cost-effective and clinically convenient for use in patient-centered care. The Lower Limb Functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 34 publications
11
33
0
1
Order By: Relevance
“…The EFA of the LLFI-PL confirmed a single-factor structure, though the presence of a possible inflection at point-2 in the scree plot suggests that a modification to the questionnaire may be necessary, such as shortening to remove potential redundant items. This is consistent with the recommendations of previous authors [11,13,14].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The EFA of the LLFI-PL confirmed a single-factor structure, though the presence of a possible inflection at point-2 in the scree plot suggests that a modification to the questionnaire may be necessary, such as shortening to remove potential redundant items. This is consistent with the recommendations of previous authors [11,13,14].…”
Section: Discussionsupporting
confidence: 93%
“…This study's results demonstrated the LLFI-PL has comparable psychometric properties to the original-English, Spanish, and Turkish versions [11,13,14]. The internal consistency (α = 0.94) is slightly higher than the original and Spanish versions (α = 0.91) [11,13] and notably more than the Turkish (α = 0.82) [14].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations